Time Characteristics of Technical Readiness of Female Triple Jumpers of High Qualification - Konestyapin, Volodymyr; Pavlos, Olha; Khanikiants, Olena; Dunets-Lesko, Antonina; Dukh, Tеtiana; Svуshch, Yaroslav (Physical Education Theory and Methodology, 2022)
Background. The relentless growth of sports results and the lack of comparative analysis of a set of indicators of technical readiness of female triple jumpers of various qualifications indicates the viability of research in this regard. The study purpose was to specify the time characteristics of technical readiness of female triple jumpers of high qualification. Materials and methods. We used the following research methods: theoretical analysis and generalization of data from scientific and methodological literature, pedagogical observation, instrumental methods (video recording) and methods of mathematical statistics. The study was conducted on the basis of investigating the time characteristics of the technical readiness of skilled triple jumpers. The pedagogical experiment took place during the competitions of the Cup of Ukraine and the Championship of Ukraine in Athletics. The study involved 9 female triple jumpers (average age 25.3 ± 5.1), including two masters of sports of international class of Ukraine, four masters of sports of Ukraine, and three candidates for masters of sports of Ukraine. Results. In the course of the study, we found that the indicators of the duration of the reference periods of the last 6 steps of the run in the triple jump by female jumpers of high qualification are characterized by a low level of variability. In terms of flight duration, the highest variability was observed in the 3rd, next to last and last steps of the run. According to the results of the study of rhythmic-tempo characteristics of a triple jump of high qualification, it was established that the highest indicators of the pace of the running step are at the last step of the run and reach 4.67 ± 0,03 st./s. The correlation between such time characteristics as the duration of the flight period of the next to last run step (r = -0.85), the rate of the next to last (r = 0.60) and last step (r = 0.78), and the rate of intensity (r = 0.76) with a sports result. In the triple jump by female jumpers of high qualification, indicators of the duration of the phases of “jump”, “step”, “jump”, their total duration and the average speed of the jumping phases are characterized by a low level of variability. The duration of the “hop” is 0.66 ± 0.06 s. The longest phase is the “jump” phase (0.78 ± 0.06 s), and the shortest is the “step” phase (0.51 ± 0.04 s). Conclusions. It was established that due to the reduction of the duration of flight periods in the last steps of the take-off, there is an increase in the take-off speed of high-skilled jumpers. The variability of the contrast between the growth rate of 31.90% and the rate of mobilization of 35.12% indicates that high-skilled jumpers use different options to combine takeoff and repulsion. Analysis of the rhythmic structure of the triple jump technique shows that all jumps are dominated by the phase of “jump” (40.05%), and the shortest is the phase of “step” (26.30%). It was found that the following time characteristics: the duration of the flight period of the next to last run step (r = -0.85), the pace of the next to last step (r = 0.60), the pace of the last step (r = 0.78), and the pace intensity (r = 0.76) have a statistically significant relationship with sports results (p < 0.05).